Lung cancer awareness training experiences of community health workers in KwaZulu-Natal, South Africa - Siyabonga B. Dlamini; Khumbulani W. Hlongwana; Themba G. Ginindza (AOSIS, 2022)
Background: Lung cancer is the leading cause of cancer mortality worldwide. Awareness interventions in the developing world remain scarce. Community health workers (CHWs) are a critical component towards ensuring efficient delivery of healthcare services in low- and middle-income countries. Aim: This study explored the experiences of CHWs of their training as lung cancer awareness intervention implementers. Setting: The study was conducted in a resource-poor setting, with CHWs from previously disadvantaged communities. Methods: On the last day of training, 10 CHWs were requested to voluntarily participate in a focus group discussion regarding their experiences of the training, utilising a discussion guide. Results: The participants expressed positive experiences with the training. They cited the amenable and conducive learning environment established by the facilitator. The participants felt empowered through the newly acquired knowledge and wanted to help their communities. However, some participants expressed a desire to have other forms of learning incorporated in future training. The participants were also cognisant of existing gaps in their own knowledge that could be elaborated upon in preparation for potential questions by the community. Some participants confirmed their role as agents of change. Conclusion: The authors propose large-scale intervention studies of lung cancer awareness utilising the CHW programme to gather conclusive evidence regarding their effectiveness at a community level. Contribution: This article provides insight into the training of community health workers on lung cancer awareness and future research on the integration of the intervention into already existing programmes.